2005
DOI: 10.1002/chin.200508191
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Absolute Configuration of a New Cyclopropanic Compound Derived from the Sesquiterpene β‐Himachalene.

Abstract: Terpenes U 0200Synthesis, Structure, and Absolute Configuration of a New Cyclopropanic Compound Derived from the Sesquiterpene β-Himachalene. -Cyclopropanation of the bridgehead double bond of β-himachalene (I) with dichlorocarbene, generated in a phase-transfer-catalytic system, followed by oxidative cleavage of the cyclohexene double bond in (III) yields the polyfunctionalized enantiopure dichlorocyclopropane (IV), which could be a valuable precursor for pyrethroid derivatives. Its absolute configuration is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…In the course of our research programs aimed at the synthesis of natural chlorinated compounds [5][6][7][8], we report here the structure of an ew organic chlorinated monoterpene. The X-ray single crystal structure analysis permits us to assign the absolute configuration of C2, C4 and C7.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of our research programs aimed at the synthesis of natural chlorinated compounds [5][6][7][8], we report here the structure of an ew organic chlorinated monoterpene. The X-ray single crystal structure analysis permits us to assign the absolute configuration of C2, C4 and C7.…”
Section: Discussionmentioning
confidence: 99%
“…For synthetic details, see: Boualy et al (2011); Dragutan et al (2007). For related structures, see: Boualy et al (2009Boualy et al ( , 2011; Ziyat et al (2004Ziyat et al ( , 2006. For the distribution of caraway (Carum carvi L.), see: Carvalho da & Fonseca da (2006); Hornok (1992).…”
Section: Related Literaturementioning
confidence: 99%
“…They are applied in the synthesis of polyfunctional acyclic and heterocyclic compounds, such as β-aminoacids (Juaristi & Soloschonok, 2005) and alkaloids (Nagashima et al, 2003). As a part of our interest in the synthesis of optically actives polyhalogenated products from terpenes (Boualy et al, 2009;Ziyat et al, 2004;Ziyat et al, 2006;Boualy et al, 2011) we report herein on the synthesis and crystal structure of the title compound. It is a new polyhalogenated terpene from (R)-carvone, which could be a valuable precursor for the synthesis of new polyfunctional terpenic compounds.…”
Section: Data Collectionmentioning
confidence: 99%
“…In our search for new functionalized and heterocyclic systems from naturally occurring terpenes (Ziyat et al, 2002(Ziyat et al, , 2004Fdil et al, 2002;Feddouli, El Kadib et al, 2004;Dakir et al, 2004), we recently reported that (1R)-thiocamphor, (1), and Cethoxycarbonylnitrilimines (2a)-(2c) react efficiently to give, diastereoselectively, the novel spiranic 1,3,4-thiadiazolines (3a)-(3c), whose structures and absolute configurations were proved beyond doubt using X-ray diffraction ) (see first scheme below). We have also commented that some of the diazolo rings reported in the literature are unstable (Huisgen et al, 2001).…”
Section: Commentmentioning
confidence: 99%